2020
DOI: 10.1371/journal.pone.0237201
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of thermal fluctuations on heat tolerance and its metabolomic basis in Arabidopsis thaliana, Drosophila melanogaster, and Orchesella cincta

Abstract: Temperature varies on a daily and seasonal scale and thermal fluctuations are predicted to become even more pronounced under future climate changes. Studies suggest that plastic responses are crucial for species’ ability to cope with thermal stress including variability in temperature, but most often laboratory studies on thermal adaptation in plant and ectotherm organisms are performed at constant temperatures and few species included. Recent studies using fluctuating thermal regimes find that thermal perform… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 106 publications
0
9
0
1
Order By: Relevance
“…Changes in polyols on the other hand have been associated with changes in heat tolerance ( Hendrix and Salvucci, 1998 ; Wolfe et al, 1998 ; Salvucci et al, 2000 ; Benoit et al, 2009 ). However, few have attempted to describe how these metabolites are affected by dynamic and fluctuating temperatures as encountered in nature (but see Kristensen et al, 2012 ; Noer et al, 2020 ; Sheldon et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in polyols on the other hand have been associated with changes in heat tolerance ( Hendrix and Salvucci, 1998 ; Wolfe et al, 1998 ; Salvucci et al, 2000 ; Benoit et al, 2009 ). However, few have attempted to describe how these metabolites are affected by dynamic and fluctuating temperatures as encountered in nature (but see Kristensen et al, 2012 ; Noer et al, 2020 ; Sheldon et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, Sørensen et al (2016) showed that the response to fluctuations is restricted to a much smaller set of genes in the transcriptomic response in contrast to mean constant temperatures, where a major part of the transcriptome is involved in the response, so it could be expected that CT max differed between both regimens. Also, Noer et al (2020) found stronger metabolome responses in thermally fluctuating conditions in Arabidopsis thaliana and Drosophila melanogaster that could be involved in heat resistance. Thus, the expression pattern of plastic responses may differ dramatically at constant and fluctuating temperatures (Podrabsky & Somero, 2004; Tomanek, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…At a given mean temperature, it has been suggested that a higher daily thermal fluctuation can lead to an increased tolerance to extreme temperature (Verheyen & Stoks, 2019). However, the effects of temporal variation of temperatures on acclimation responses of metabolism and other functional processes are often species dependent in ectotherms (Niehaus et al., 2011; Noer et al., 2020), and can also interact with changes in mean temperature (Bozinovic et al., 2011; Colinet et al., 2015). Further studies are required to elucidate whether acclimation responses of SMR and other functional traits in asp vipers are causally linked with changes in mean temperature, changes in the thermal variability or both.…”
Section: Discussionmentioning
confidence: 99%